Machine Learning with Metaheuristic Algorithms for Sustainable Water Resources Management - Kisi, Ozgur (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The main aim of this book is to present various implementations of ML methods and metaheuristic algorithms to improve modelling and prediction hydrological and water resources phenomena having vital importance in water resource management.